The Pathology of Intestinal Mucosal Disruption; Implications for Muscle Loss and Physical Dependency from Late Adolescence to Octogenarians - Qaisar R; Karim A; Iqbal MS; Muhammad T; Ahmad F; Alkahtani SA (International Journal of General Medicine)
Rizwan Qaisar,1– 3 Asima Karim,1 M Shahid Iqbal,4 Tahir Muhammad,5 Firdos Ahmad,1– 3 Shaea A Alkahtani6 1Basic Medical Sciences, College of Medicine, University of Sharjah, Sharjah, United Arab Emirates; 2Space Medicine Research Group, Sharjah Institute for Medical and Health Sciences, University of Sharjah, Sharjah, 27272, United Arab Emirates; 3Cardiovascular Research Group, Sharjah Institute for Medical and Health Sciences, University of Sharjah, Sharjah, 27272, United Arab Emirates; 4Department of Neurology and Stroke Medicine, Rehman Medical Institute, Peshawar, 25124, Pakistan; 5Department of Biochemistry, Gomal Medical College, Dera Ismail Khan, Pakistan; 6Exercise Physiology Department, College of Sport Sciences and Physical Activity, King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Shaea A Alkahtani, College of Sport Sciences and Physical Activity, King Saud University, PO Box: 1949, Riyadh, 11451, Saudi Arabia, Tel +966118063040, Fax +966118063370, Email shalkahtani@ksu.edu.saBackground and Objectives: A pathological increase in intestinal permeability causes muscle loss and physical decline by inducing systemic inflammation and oxidative stress. However, most relevant studies investigate older adults, and the appropriate data across age spans remain elusive. This study aimed to examine the associations of intestinal permeability with muscle loss and physical decline across a large span of ages. We measured plasma zonulin, a marker of increased intestinal permeability, from adolescents to octogenarians in association with muscle health and gait speed.Research Methods and Procedures: In this cross-sectional, observational study, we recruited healthy men, including young (age=18-35 years, n=135), middle-aged (age=35-59 years, n=118), and older (age=60-90 years, n=163) adults for evaluating - handgrip strength (HGS), skeletal muscle mass index (SMI), and gait speed. We also measured plasma zonulin, c-reactive proteins (CRP), and 8—isoprostanes using ELISA assays.Results: Plasma zonulin gradually increased from young and middle-aged to older adults (all p< 0.05). Conversely, HGS and gait speed were progressively reduced from young and middle-aged to older adults (all p< 0.05). In addition, older adults also exhibited lower SMI than young and middle-aged men (both p< 0.05). Plasma zonulin exhibited significant negative correlations with HGS and gait speed and positive correlations with CRP and 8-isoprostanes in middle-aged and older men (all p< 0.05). We also found significant areas under the curve for the efficacy of plasma zonulin in diagnosing low HGS (< 27kg) and gait speed (0.8 m/s). After adjustment for age, plasma zonulin demonstrated robust negative correlations with HGS and gait speed and positive correlations with CRP and 8-isoprostanes in the cumulative cohort.Conclusion: Altogether, an increasing intestinal leak from middle age onward contributes to muscle weakness and physical decline. Our data is clinically relevant in understanding and treating physical dependency in middle-aged and older adults.Keywords: Handgrip strength, zonulin, intestinal permeability, gait speed